(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
The article examines the multifaceted role of translation within the sphere of intercultural communication, demonstrating that translation functions not as a mere linguistic operation but as a dynamic act of cultural mediation. Drawing on interdisciplinary theoretical frameworks, the study explores how translators navigate the complex interplay between language structures, cultural values, and pragmatic conventions. The analysis reveals that translation involves the reconstruction of meaning rather than its replication, requiring translators to exercise intercultural sensitivity, cognitive adaptability, and ethical discernment. It is argued that translation actively reshapes the conditions of intercultural interaction, contributing not only to mutual intelligibility but also to the emergence of hybrid cultural forms within an increasingly interconnected global environment.